Surgical morbidity associated with total laparoscopic hysterectomy in women with prior diagnostic excision of the cervix - Chailert Phongnarisorn (2018)
Aims: To evaluate the feasibility, safety, and complications of total laparoscopic hysterectomy (TLH) in women undergoing prior diagnostic excision of the cervix. Methods: A retrospective study (Canadian Task Force classification II-2) was conducted in a tertiary care university hospital. The medical records of women undergoing TLH between June 2003 and September 2004 were reviewed. Results: Twenty-six women with stage IA1 cervical cancer (19) and persistent high grade cervical neoplasia (7) underwent TLH after diagnostic cervical excision. The operation was successfully performed in all cases without conversion to laparotomy. The mean age of the patients was 47.0 ± 8.64 years (95% CI 43.5-50.5). 19 patients had previous loop electrosurgical excision procedure (LEEP), one had cold knife conization. Six patients underwent repeated LEEP for positive endocervical margin. The mean operating time was 253.0 ± 66.7 min (95% CI 226.0-279.9). The median blood loss was 300 mL (range 50-1000 mL). Only one patient needed 1 unit of blood transfusion. The median post-operative hospital stay was 3 days (range 2-6 days). All hysterectomy specimens had negative surgical margins. Two patients had major complications, one with bladder injury requiring laparoscopic repair. The remaining one had ureteral injury detected 9 days after the operation requiring subsequent ureteroneocystostomy. Both complications occurred in the first four cases of this series. No significant morbidity was noted in 2 years of follow-up. Conclusion: TLH appears to be feasible and safe in patients with prior diagnostic excision of the cervix. Careful separation of the bladder from the cervix and identification of both ureters are recommended to minimize morbidity associated with this operation. © 2007 The Authors.